Point pattern analysis of thermal anomalies in geothermal fields and its use for inferring shallow hydrological processes. (May 2023) - Rodriguez-Gomez, Cecilia; Kereszturi, Gabor; Whitehead, Melody; Reeves, Robert; Rae, Andrew; Pullanagari, Reddy
Highlight: Point pattern analyses applied to thermal anomalies of a geothermal area. From which shallow permeability and heat movement are inferred. Two broad regions can be identified which present distinct subsurface conditions. Abstract: Geothermal areas are studied with a diversity of techniques, including remote sensing (e.g. hyperspectral and thermal imagery) which can provide a time and cost efficient method to assess the surface of geothermal areas and infer subsurface processes. This study presents the analysis of thermal anomalies extracted from a single thermal infrared image covering Waiotapu Geothermal Field, New Zealand. Point pattern analyses were undertaken to assess any dominant orientations, and departures from randomness based on anomaly locations. The thermal anomalies present orientations that approximately align with nearby active faults, suggesting fault control in the Waiotapu Geothermal Field. Two distinct regions were observed, northern areas and southern areas. Northern areas show higher temperatures (i.e. >47 C°) and lower densities of thermal anomalies, with an orientation close to that of the whole field (∼ N22E°) and separation within cluster separations of ∼250 m, signalling to a high content of clays and proximity to the heat source. Southern areas exhibit lower temperatures (i.e. <47 C°) and a higher density of clustered thermal anomalies in a variety of orientations with clustering at all distances, indicating higher permeability at shallow depths. This is likely caused by a thinner litho-cap layer and a history of hydrothermal eruptions and collapse craters. Thermal imagery can therefore be used to infer the subsurface processes taking place at geothermal areas, elucidating information about the shallow permeability and heat movement. Our method can be applied to any other geothermal field for exploration to understand the shallow substrate and its control on porosity and permeability structure.